Multiple point compression on curves - Fan, X.; Otemissov, A.; Sica, F.; Sidorenko, A. (Nazarbayev University, 2014)
Multiple point compression is an important feature to improve the implementation of elliptic curve cryptography. This can be extended to other curves, in particular hyperelliptic curves, with divisors represented in Mumford form.
Keywords: multiple point; elliptic curve cryptography; particular hyperelliptic curves; methods